Children and Adolescents' Mental Health Following COVID-19: The Possible Role of Difficulty in Emotional Regulation - Hen, Meirav; Shenaar-Golan, Vered; Yatzker, Uri (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic has shattered routines throughout the world, creating closures and social isolation. Preliminary studies conducted during the pandemic have shown that children and adolescents are mainly affected by social distancing and the lack of a supportive framework. The purpose of the present study was to compare mental health symptoms of children and adolescents who sought mental health services in the community before vs. during the pandemic. The study examined children’s perceived burden of the pandemic, reports of emotional and behavioral problems (SDQ) anxiety (SCARED), depressed moods (SMFQ-P), and difficulty in emotional regulation (DERS), as well as intervening variables such as age and gender. Furthermore, the effect of difficulty in emotional regulation on children’s mental health symptoms was explored. Findings indicate an increase in all mental health symptoms excluding anxiety, during the pandemic. Boys reported more difficulty in emotional regulation during the pandemic than before, and girls reported more emotional and behavioral problems. Children reported an increase in emotional and behavioral problems and adolescents in peer relationship problems. Difficulty in emotional regulation predicted all mental health symptoms in both samples, more so in girls and adolescents. These initial findings support the need for further studies to examine the long-term mental health effects of Covid-19 pandemic on children and adolescents.